Effets des adventices de l’ananas sur "Pratylenchus brachyurus" en Côte d’Ivoire - Gnonhouri, Goly Philippe; Téhé, Henri (Cahiers Agricultures, 1997)
The roots of weeds grown in pineapple fields were examinated for the presence of the nematode Pratylenchus brachyurus. Of the 55 plant species analysed, belonging to 26 familles, 15 species were infected by P. brachyurus, including Bidens pilosa, Emilia coccinea, Ipomea nil, Oldalendia affinis, Secamone afzelei, Solanum torvum and Tristemma coronata in which such infections have not been previously reported. The results highlighted the polyphagy of P. brachyurus and the limits of wild fallows for soil rehabilitation between two pineapple crop cycles. The pantropical weed Chromolaena odorata is beneficial as it is not affected by P. brachyurus, and it can quickly and abundantly overrun spontaneous fallows in Côte d’Ivoire.